Information Quality and Options - Vanden, Joel M. (Review of Financial Studies, 2008)
Microstructure researchers have long understood that information quality has an effect on price formation in the underlying asset market. However, option researchers have largely ignored the fact that information quality might also impact the options market. This article characterizes the nature of the impact by showing how option prices and implied volatility levels are related to the forward looking information quality path. This result follows from a noisy rational expectations model that abandons the normal distribution in favor of the gamma distribution, but maintains the standard assumption of exponential utility. Thus the new model bridges the gap between the microstructure literature that relies so heavily on the normal-exponential framework, and the options literature that relies exclusively on models that are consistent with the limited liability of stock prices. The model's tractability allows for a robustness check against the standard framework and provides a viable setting for analyzing the empirical implications of information quality for the options market. The Author 2007. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please email: journals.permissions@oxfordjournals.org., Oxford University Press.